A Comprehensive Systematic Review of The Relationship Between The Duration of Catheterization And The Risk of Urinary Tract Infection Following Ureteroplasty - Peter Darmawan (The International Journal of Medical Science and Health Research, 2026)
Introduction: Urinary tract infection (UTI) is a prevalent and consequential complication following urological surgeries involving catheterization, such as ureteroplasty. The duration of catheterization is a modifiable risk factor, yet optimal timing for catheter or stent removal to balance the risks of UTI against other surgical complications remains a significant clinical question (Visser et al., 2019). Methods: This systematic review synthesized evidence from 66 studies. A comprehensive search and screening process identified studies reporting on the relationship between catheterization duration and UTI risk in patients undergoing ureteroplasty and related urological procedures. Data on study design, population, catheterization details, UTI definitions, and outcomes were extracted and analyzed qualitatively and quantitatively where possible. Results: The synthesis demonstrates a strong, dose-dependent relationship between longer catheterization duration and increased UTI risk. Meta-analyses consistently showed that early stent removal (typically defined as ≤3 weeks) significantly reduces UTI incidence compared to later removal, with odds ratios ranging from 0.41 to 0.53 (Visser et al., 2019; Kusuma et al., 2025; Oka et al., 2020). Primary studies in kidney transplantation reported UTI rates of 2-10% with early removal (1-2 weeks) versus 25-35% with late removal (4-6 weeks) (Indu et al., 2012; Coskun et al., 2011; Ramamoorthy et al., 2018). Evidence from ureteroplasty and general urology settings supports a similar trend, with each additional day of catheterization increasing risk. Bacterial colonization of devices, a precursor to infection, rises significantly with time (Bouassida et al., 2023; Toprak et al., 2020). Discussion: The findings underscore that prolonged catheterization facilitates biofilm formation and bacterial ascension, leading to UTIs. The relationship exhibits threshold effects, with notable risk increases beyond 7, 14, and 30 days depending on the clinical context. While most evidence originates from kidney transplant populations, the biological mechanism is applicable to ureteroplasty. Confounding factors like female gender, diabetes, and lack of antibiotic prophylaxis modulate this risk (Hosseinpour et al., 2023; Marschall et al., 2013). Conclusion: Shorter durations of urinary catheterization and ureteral stenting are strongly associated with a lower risk of postoperative UTI without increasing major urological complications. For ureteroplasty and similar reconstructive procedures, adopting a protocol for early catheter removal (within 2-3 weeks where surgically safe) is recommended. Future research should focus on procedure-specific RCTs in ureteroplasty populations to refine optimal duration guidelines.